At bebo kunsten - lokale og globale rum og praksisser for beboelse af det sanselige og poetiske - Worre Hallberg, Gry (Peripeti, 2022)
The inhabiting of art. Local and global practices for inhabitation of the sensuous and poetic This essay explores the intersection of aesthetics and ecology in the author’s artistic works with Sisters Hope. It is in continuation of the findings in her PhD dissertation, in which she investigates how sustainability may be attained through stimulation of an ecological awareness, which the aesthetic, evoked through contemporary art processes, can arouse.